Correlation between the Mini Mental State Examination-Korean version and the Measurement of Quality of the Environment in the institutionalized elderly - Kim, Myoung-Kwon (J Phys Ther Sci, 2015)
[Purpose] This study aimed to investigate the correlation between the cognitive level of the elderly and their attitude towards the living environment. [Subjects and Methods] A total of 80 elderly people hospitalized in a nursing home in K city, South Korea, participated in this study. Pearson correlation analysis was used to test the relationships between scores on the Mini Mental State Examination-Korean Version and Measurement of Quality of the Environment (facilitators and obstacles). [Results] A positive and moderately strong correlation (r = 0.462) was found between scores on the Mini Mental State Examination and the Measurement of Quality of the Environment (obstacle). [Conclusion] In a nursing home, patients with relatively higher cognitive levels can perceive more obstacles in the surrounding environment.